Penerapan Strategi Bisnis Pada UMKM Secara Digitalisasi Di Desa Wage Kecamatan Taman Sidoarjo - Untung Lasiyono; Tony Susilo Wibowo; Nashrudin Latif; Widiar Onny Kurniawan; Taudlikhul Afkar (Ekobis Abdimas, 2023)
The job of Micro, Small and Medium Enterprises in turning the wheels of the Indonesian economy is evident, however there are as yet numerous obstructions so the improvement of MSMEs is as yet not true to form. One of the variables is that there is no business legitimateness for most MSMEs in the district. In the ongoing time of data innovation, MSMEs really can possibly grow the market by selling on the web, yet the restricted information about internet based deals makes this potential be not taken advantage of appropriately. This people group administration action looks to give a comprehension of the advantages of business legitimateness and how to utilize correspondence media to make deals on the web. It is trusted that by having business legitimateness, MSME entertainers can get to direction from applicable government offices and can get to credit from banks. With the range of online deals, it is trusted that the turnover of MSMEs can increment essentially.